(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the prevalence of preoperative anxiety and its related factors among patients scheduled for elective surgery. Methods: A cross-sectional study was conducted on 85 patients (≥16 years) undergoing elective surgery at the Department of Anesthesiology and Intensive Care, Transport Hospital, from August 2024 to March 2025. Data were collected using a structured questionnaire and analyzed with SPSS 20.0. Results: The prevalence of preoperative anxiety was 56.5%. Higher anxiety was significantly associated with female gender (72.7%), no previous surgical experience (61.4%), and surgeries in Trauma (73.7%) and Obstetrics (71.4%) (p<0.05). The most common concern was fear of pain (55.3%). No significant differences were found by age, occupation, or education level. Conclusion: Preoperative anxiety remains prevalent at Transport Hospital, particularly among females and patients undergoing trauma or obstetric surgery. Enhanced preoperative counseling, especially regarding pain management, is recommended to improve patient experience and surgical safety.